Pengaruh Jumlah Polimer terhadap Karakteristik Fisik dan Pelepasan Nanopartikel Fraksi Diterpen Lakton Sambiloto - Kitosan - Sari, Retno; Paramanandana, Abhimata; Isadiartuti, Dewi; Rahayyu, Annisa Maulidia (Fakultas Farmasi Universitas Andalas, 2020)
The diterpene lactone fraction of Andrographis paniculata Nees (sambiloto) (FDTLS) main compound is andrographolide. Andrographolide has poor bioavailability, high lipophilicity, and low solubility. Entrapping poorly soluble substances into a hydrophilic polymer, such as chitosan, could improve their dissolution, bioavailability, and activity. The purposes of this study were to improve the FDTLS dissolution and to compare the effect of different amounts of chitosan on physical characteristics, entrapment efficiency, and FDTLS release from nanoparticles, which was made by the ionic gelation-spray drying method using tripolyphosphate as a crosslinker. The nanoparticles were prepared with different FDTLS-chitosan ratios = 1:2 (FK1), 1:2.5 (FK2) and 1:3 (FK3). The nanoparticles were evaluated for its morphology, physical state using differential thermal analysis (DTA), Fourier-transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), entrapment efficiency, and drug release. All the nanoparticles' formulas had a spherical shape and FK2 showed the smoothest surface with the highest enthalpy. FDTLS-chitosan nanoparticles diffractogram showed a more amorphous form. The FDTLS-chitosan nanoparticles entrapment efficiency was 29.01-32.69%. The FDTLS-chitosan nanoparticles showed an increased dissolution rate by 1.6 times compared to the FDTLS substance. The study concludes that the formation of nanoparticles using chitosan by ionic gelation-spray dry method could improve the dissolution of FDTLS.